1999
DOI: 10.2337/diabetes.48.5.1138
|View full text |Cite
|
Sign up to set email alerts
|

Significance of glutathione-dependent antioxidant system in diabetes-induced embryonic malformations.

Abstract: Hyperglycemia-induced embryonic malformations may be due to an increase in radical formation and depletion of intracellular glutathione (GSH) in embryonic tissues. In the past, we have investigated the role of the glutathione-dependent antioxidant system and GSH on diabetes-related embryonic malformations. Embryos from streptozotocin-induced diabetic rats on gestational day 11 showed a significantly higher frequency of embryonic malformations (neural lesions 21.5 vs. 2.8%, P<0.001; nonneural lesions 47.4 vs. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 0 publications
1
76
0
1
Order By: Relevance
“…Recently, the deleterious effect of oxidant stress on Pax DNA binding was also demonstrated for Pax3 (56a). The involvement of reactive oxygen species in diabetic embryopathy is supported by studies demonstrating amelioration of congenital malformations with antioxidants (57)(58)(59). Additionally, a rat substrain resistant to dysmorphogenesis produced by maternal diabetes has been shown to have increased levels of both superoxide dismutase and catalase mRNA when compared with a more sensitive substrain (60).…”
Section: Discussionmentioning
confidence: 57%
“…Recently, the deleterious effect of oxidant stress on Pax DNA binding was also demonstrated for Pax3 (56a). The involvement of reactive oxygen species in diabetic embryopathy is supported by studies demonstrating amelioration of congenital malformations with antioxidants (57)(58)(59). Additionally, a rat substrain resistant to dysmorphogenesis produced by maternal diabetes has been shown to have increased levels of both superoxide dismutase and catalase mRNA when compared with a more sensitive substrain (60).…”
Section: Discussionmentioning
confidence: 57%
“…The congenital malformations associated with diabetic pregnancy affect many major organs, including the central nervous, cardiovascular, gastrointestinal, urogenital and musculoskeletal systems [5,6]. The pathogenesis of congenital anomalies is complex and still poorly understood, although it has been suggested that excessive reactive oxygen species (ROS) associated with hyperglycaemia are responsible for the increased risk of malformation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of ROS involvement in hyperglycemia-induced embryopathy was first obtained in studies in which antioxidant enzymes proved to be protective in vitro (18,19). Increased ROS production (20,21) and lipid peroxidation (22) have subsequently been found in rat embryos cultured in high glucose and in embryos of diabetic rat mothers. Enzymatically produced ROS can disturb embryo development in vitro similarly to the effect of high glucose (23), and the resulting maldevelopment can be blocked by vitamins E and C separately (24).…”
mentioning
confidence: 99%